Influence of deficit irrigation and canopy structure on water stress management of Touriga Nacional (Vitis vinifera L.) in Douro Demarcated Region - Damasceno, Ana Flávia Bonatto (2022)
Mestrado de dupla diplomação com a UTFPR - Universidade Tecnológica Federal do Paraná